Pengaruh Return On Assets(ROA) Dan return On Equity(ROE) terhadap Kinerja Kesehatan Capital Adequacy Ratio(CAR) Pada Bank BTPN - harun Al Rasyid Al Rasyid; Suryanto Sosrowidigdo (Politeknik Ganesha Medan, 2022)
Banking is currently being demanded to be able to increase its profitability because profitability is the net end result of various management policies and decisions. This ratio describes the level of effectiveness in managing banking assets if the profit generated by the bank is high it will also have an impact on own capital which can improve the health of the bank related to the Capital Adequacy Ratio (CAR). The research method used is multiple linear regression analysis method. The type of research used is quantitative research. Source of data is secondary data. The data collection technique is a documentation technique. Data processing using SPSS 16. Data analysis used included descriptive test, classical assumption test, multiple linear regression test, hypothesis test, and coefficient of determination test. Hypothesis testing using t test shows that: 1) Return on Assets (ROA) has a positive and significant effect on the Capital Adequacy Ratio (CAR); 2) Return On Equity (ROE) does not have a positive effect on the Capital Adequacy Ratio (CAR); and 3) the F test is known that simultaneously Return On Assets (ROA), Return On Equity (ROE) have a significant positive effect on the Capital Adequacy Ratio (CAR). Then the coefficient of determination (R2) is 0.172 or 17.2%. This means that the contribution of Return On Assets (ROA), Return On Equity (ROE) to Bank BTPN's Capital Adequacy Ratio (CAR) is 84.1%, while the remaining 15.9% is explained by other variables.